Prehospital antibiotics and intravenous fluids for patients with sepsis: protocol for a 2×2 factorial randomised controlled trial - Nick Daneman; Tony Mazzulli; Rob Stenstrom; Gail Klein; Ruxandra Pinto; Lisa Burry; Sheldon Cheskes; Jim Christenson; Damon C. Scales; Anna Rogowsky; Ian R. Drennan; Morgan Hillier; et al. (BMJ Open)
Introduction Prompt recognition and treatment of patients with sepsis improve survival. Patients transported to hospital with sepsis often do not receive treatment until they are assessed in emergency departments. Initiation of treatments by paramedics at the point of first contact may improve outcomes for these patients.Methods and analysis The study design involves two randomised controlled trials (RCTs) conducted using a 2×2 factorial design comparing use of (1) early intramuscular ceftriaxone versus placebo and (2) an early liberal intravenous fluid strategy (up to 2 L normal saline) versus usual care resuscitation guided by paramedic medical directives. Patients who are ≥18 years of age will be eligible for inclusion if they have sepsis, defined as (1) paramedic suspicion of infection, (2) fever (temperature ≥38.0°C measured by paramedic or history of fever during the previous 24 hours), and (3) hypotension: SBP <100 mm Hg. The primary outcome is mortality prior to hospital discharge or within 90 days of admission. Secondary outcomes are all-cause mortality at 90 days after enrolment; organ dysfunction during first 24 hours (mechanical ventilation, vasopressor therapy, dialysis) and hospitalisation (mechanical ventilation; dialysis); rates and duration of hospital admission; rates of ICU admission during index hospitalisation; discharge destination; proportion of patients with positive blood cultures obtained in hospital (first 24 hours); microbiological profile including distribution of microorganism species and resistant organisms; proportion of patients receiving additional antibiotics within 6 hours and within 24 hours of hospital admission; frequency distribution of first antibiotics (if any) delivered within 24 hours of hospital arrival; mean time to antibiotics delivered within 24 hours of hospital arrival (if any); proportion of patients receiving fluid bolus (>250 mL) within 24 hours of hospital arrival; total amount of crystalloid infused during transport and first 24 hours of hospitalisation; and proportion of enrolled patients not suspected to have sepsis or infection by emergency department physicians. Safety outcomes include the proportion of patients with pulmonary oedema during transport to hospital and on initial chest X-ray and the proportion of patients with anaphylaxis or suspected allergic reactions to study medication.Ethics and dissemination This study has been approved through Clinical Trials Ontario’s streamlined ethics review process (board of record, Sunnybrook Health Sciences Centre). It will be conducted in accordance with the Declaration of Helsinki, Good Clinical Practice guidelines and regulatory requirements. The final results will be disseminated to participating paramedic services through educational materials, presentations and interactive training. We anticipate our trial will achieve wide dissemination through publication in a peer-reviewed medical journal and presentation at international conferences targeting the fields of prehospital and emergency medicine, resuscitation and critical care.Trial registration number NCT03068741.